Kesenjangan Hukum Dan Realitas Sosial Dalam Transaksi Tanah Tanpa Sertifikat - Bintang Idrus, Muhammad; Ch. Thalib, Mutia; Hidayat Muhtar, Mohamad (Cv. Kalimasada Group, 2025)
Land buying and selling transactions without certificates still occur frequently in society due to limited access to formal land certification processes. This study aims to analyze the form of legal protection for buyers in land sale and purchase transactions that have not been certified, and to offer a new approach model in the form of intermediate legal recognition to overcome limited access to the formal land registration process. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach, and refers to primary legal materials such as UUPA No. 5 of 1960 and PP No. 24 of 1997. The results of the study indicate that although land sale and purchase transactions without certificates can be declared valid in civil law, the absence of a certificate weakens the legal position of the buyer, especially in terms of proving ownership rights before the law. The temporary legal recognition model based on village administrative documents is considered to be a transitional solution that provides preventive protection while strengthening the drive to follow the land certification process in full. This approach also reflects the need for land law reform that is more responsive to the social and economic conditions of the community. The results found that the absence of a certificate weakens the legal position of the buyer, so a temporary legal recognition model based on village administrative documents is needed as transitional protection.